I love the smell of napalm in the morning: aesthetics against society. Issue 2 (3rd July 2017) - Pinney, Christopher
Abstract : The relationship of aesthetics to ethics is explored through a discussion of late nineteenth- and early twentieth-century Japanese military woodblock prints and recent Daesh (ISIL) media productions. Ruth Benedict's The Chrysanthemum and the Sword is praised for its anthropological 'nearness' to a 'dangerous' local aesthetics and ethics, a 'proximity' that philosophers of aesthetics seem reluctant to entertain. Thierry de Duve's engagement with Kant's sensus communis (which creates the 'oughtness' of art) is invoked to help explain why politics is always inextricably aestheticized and aesthetics always intrinsically political.